BRIEF GUIDELINES FOR DESCRIPTION OF THE DIAGNOSTIC STUDY RESULTS - Ruslan T. Saygitov; Anastasiya S. Ostrovskaya (Вопросы современной педиатрии, 2017)
We bring to the attention of the authors brief guidelines for preparation of manuscripts containing description of the results of diagnostic studies. More detailed explanations are given in the corresponding template (http://vsp.spr-journal.ru/jour/about/submissions). Presentation  of  the  manuscript  in  the  format  of  the  specified  template  is  a  prerequisite  for  its  consideration  and  subsequent publication in the journal «Current Pediatrics» («Voprosy sovremennoi pediatrii»).